Pragmatic randomised controlled trial of a personalised intervention for carers of people requiring home oxygen therapy. (3rd January 2020) - Frith, Peter; Sladek, Ruth; Woodman, Richard; Effing, Tanja; Bradley, Sandra; van Asten, Suzanne; Jones, Tina; Hnin, Khin; Luszcz, Mary; Cafarella, Paul; Eckermann, Simon; Rowett, Debra; et al.
We used a pragmatic randomised controlled trial to evaluate a behavioural change strategy targeting carers of chronically hypoxaemic patients using long-term home oxygen therapy. Intervention group carers participated in personalised educational sessions focusing on motivating carers to take actions to assist patients. All patients received usual care. Effectiveness was measured through a composite event of patient survival to hospitalisation, residential care admission or death to 12 months. Secondary outcomes at baseline, 3, 6 and 12 months included carer and patient emotional and physical well-being. No difference between intervention ( n = 100) and control ( n = 97) patients was found for the composite outcome (hazard ratio (HR) 1.22, 95% confidence interval (CI) = 0.89, 1.68; p = 0.22). Improved fatigue, mastery, vitality and general health occurred in intervention group patients (all p values < 0.05). No benefits were seen in carer outcomes. Mortality was significantly higher in intervention patients (HR = 2.01, 95% CI = 1.00, 4.14; p = 0.05; adjusted for Australia-modified Karnofsky Performance Status), with a significant diagnosis–intervention interaction ( p = 0.028) showing higher mortality in patients with COPD (HR 4.26; 95% CI = 1.60, 11.35) but not those with interstitial lung disease (HR 0.83; 95% CI = 0.28, 2.46). No difference was detected in the primary outcome, but patient mortality was higher when carers had received the intervention, especially in the most disabled patients. Trials examining behavioural change interventions in severe disease should stratify for functionality, and both risks and benefits should be independently monitored.Trial registration: Australian New Zealand Clinical Trials Registry (ACTRN12607000177459).